Production rate calibration for cosmogenic 10 Be in pyroxene by applying a rapid fusion method to 10 Be-saturated samples from the Transantarctic Mountains, Antarctica - M. Bergelin; G. Balco; L. B. Corbett; P. R. Bierman (Geochronology, 2024)
Measurements of multiple cosmogenic nuclides in a single sample are valuable for various applications of cosmogenic nuclide exposure dating and allow for correcting exposure ages for surface weathering and erosion and establishing exposure–burial history. Here we provide advances in the measurement of cosmogenic 10 Be in pyroxene and constraints on the production rate that provide new opportunities for measurements of multi-nuclide systems, such as 10 Be / 3 He <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="50pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="a60cc47cf56b687731b9b02dbaa2690b"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="gchron-6-491-2024-ie00001.svg" width="50pt" height="15pt" src="gchron-6-491-2024-ie00001.png"/></svg:svg> , in pyroxene-bearing samples. We extracted and measured cosmogenic 10 Be in pyroxene from two sets of Ferrar Dolerite samples collected from the Transantarctic Mountains in Antarctica. One set of samples has 10 Be concentrations close to saturation, which allows for the production rate calibration of 10 Be in pyroxene by assuming production–decay equilibrium. The other set of samples, which has a more recent exposure history, is used to determine if a rapid fusion method can be successfully applied to samples with Holocene to Last Glacial Maximum exposure ages. From measured 10 Be concentrations in the near-saturation sample set we find the production rate of 10 Be in pyroxene to be 3.74 ± 0.10 atoms g −1 yr −1 , which is consistent with 10 Be / 3 He <svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="50pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="53793ac25b900b6db862427d22828cdf"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="gchron-6-491-2024-ie00002.svg" width="50pt" height="15pt" src="gchron-6-491-2024-ie00002.png"/></svg:svg> paired nuclide ratios from samples assumed to have simple exposure. Given the high 10 Be concentration measured in this sample ...